Natural Coatings for Shelf-Life Enhancement and Quality Maintenance of Fresh Fruits and Vegetables - A Review - Mahajan, Bal Vipan Chander; Tandon, Ritu; Kapoor, Swati; Sidhu, Mohinder Kaur (Journal of Postharvest Technology, 2017)
The ever increasing demand for fresh fruits and vegetables challenges the researchers and industry to develop advanced methods for  maintaining food quality and enhancing shelf life. The consumers around the globe demand chemical free fresh fruits and vegetables with high  quality, nutritional value and extended shelf life. The application of edible films and coatings to fruits and vegetables represents an  environment friendly approach to solve this problem. The use of edible coatings helps to reduce or eliminate the risk of adulteration thereby,  present food in a hygienic and aesthetically attractive way. The strategy behind the use of coatings is combination of food chemistry and  preservation technology. This review covers various types of edible coatings and their effects on the overall quality of whole and fresh cut  fruits and vegetables providing an understanding of main functions and beneficial effects of each type of coating.
Keywords: aloevera; cellulose; essential oils; herbal extract; lipid; nanoemulsion; starch